2021
DOI: 10.1021/acsapm.1c01157
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Doping by Polymer Grafting: Size Distribution Matters

Abstract: Phosphorus δ-layers in SiO 2 have been prepared by means of poly(methyl methacrylate) (PMMA), terminated with a phosphoruscontaining moiety acting as an anchoring group. In particular, grafting of two P-terminated PMMA samples with M n = 7.5 kg/mol (D̵ = 1.14) and M n = 17.8 kg/mol (D̵ = 1.23) onto 10 nm thick SiO 2 films deposited on Si substrates has been investigated, focusing on the thickness evolution of the brush layer as a function of the processing parameters, that is, annealing temperature and time. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…At the same time, simulations highlight a correlation between the composition of the brush layer and the area occupied by the polymer chains with the reactive chain-end close to the surface, suggesting that the enrichment of short chains during the grafting to process could be not simply related to the number of short and long chains at the interface, but also related to other variables, as the position of the chain term-inals or the accessible reactive areas (see the ESI † for further details). In a recent paper, 50 Perego et al reported clear evidence of preferential grafting of the short polymer chains over the long ones for homopolymers terminated with a reactive phosphorus containing moiety. However, these polymers exhibit a very different evolution of the brush layer composition as a function of time compared to the hydroxy terminated statistical copolymers that were investigated in the present work.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, simulations highlight a correlation between the composition of the brush layer and the area occupied by the polymer chains with the reactive chain-end close to the surface, suggesting that the enrichment of short chains during the grafting to process could be not simply related to the number of short and long chains at the interface, but also related to other variables, as the position of the chain term-inals or the accessible reactive areas (see the ESI † for further details). In a recent paper, 50 Perego et al reported clear evidence of preferential grafting of the short polymer chains over the long ones for homopolymers terminated with a reactive phosphorus containing moiety. However, these polymers exhibit a very different evolution of the brush layer composition as a function of time compared to the hydroxy terminated statistical copolymers that were investigated in the present work.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…The combination of the above effects is likely to explain the recently described deviation of the grafting density and the brush thickness from their usual affine and parallel increase as a function of time. 27…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Relatively good control over the dopant atom concentration was demonstrated, 16 and efficient injection and activation of the dopant in the semiconductor substrate were attained. 18,19 However, recent investigations revealed that the "graf ting to" reaction is much more complex 20 than usually believed with a shift from a diffusion-controlled to a mechanochemical driven mechanism. 21 Moreover, partitioning by molecular weight takes place at interfaces in which the lower molecular weight species are preferably incorporated into the polymeric brush.…”
Section: Introductionmentioning
confidence: 99%
“…22−25 Depending on the specific chemistry of the "grafting to" reaction, this preferential incorporation operates also in the case of polymeric dopants with dispersity Đ < 1.1, featuring relatively narrow molecular weight distributions. 20 These effects limit the capability to effectively control the number of polymer chains in the brush layer, reducing at the end the control on the dose of dopant atoms in the source.…”
Section: Introductionmentioning
confidence: 99%